Benign coronary perforation during percutaneous transluminal coronary angioplasty. Issue 1 (July 1985) - Meier, B
Abstract : In two patients percutaneous transluminal coronary angioplasty was complicated by coronary perforation. In both cases the complication was managed conservatively.